1985
DOI: 10.1111/j.1432-1033.1985.tb08629.x
|View full text |Cite
|
Sign up to set email alerts
|

Fusion of erythrocyte ghosts induced by calcium phosphate

Abstract: Using an assay which allows continuous monitoring of the mixing of aqueous contents during membrane fusion, we have investigated the kinetics of calcium-phosphate-induced fusion of erythrocyte ghosts. In the presence of 10 mM phosphate, the threshold concentration for Ca2+-induced fusion was 1.25 mM, while the optimal concentration was approx. 1.75 mM Ca2+. Further enhancement of the cation concentration ( 2 2 mM) inhibited fusion of the ghosts. Initiation of fusion required the addition of phosphate prior to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

1985
1985
2002
2002

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 44 publications
0
6
1
Order By: Relevance
“…This may be somewhat surprising since it has been previously shown that phosphate reduces the Ca2+ threshold required to induce fusion 3 The relative fluorescence of NBD-labeled lipids is unaffected by buffer composition in the presence of Triton X-100 (unpublished observations). of PS-containing vesicles (Fraley et al, 1980) and RBC ghosts (Hoekstra et al, 1985). However, Hoekstra et al (1985) have recently shown that the potential for Ca2+ and phosphate to induce fusion of RBC ghosts is extremely sensitive to the Ca2+ and phosphate concentrations and required at least 7 mM phosphate, while Ca2+ above 2 mM was inhibitory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be somewhat surprising since it has been previously shown that phosphate reduces the Ca2+ threshold required to induce fusion 3 The relative fluorescence of NBD-labeled lipids is unaffected by buffer composition in the presence of Triton X-100 (unpublished observations). of PS-containing vesicles (Fraley et al, 1980) and RBC ghosts (Hoekstra et al, 1985). However, Hoekstra et al (1985) have recently shown that the potential for Ca2+ and phosphate to induce fusion of RBC ghosts is extremely sensitive to the Ca2+ and phosphate concentrations and required at least 7 mM phosphate, while Ca2+ above 2 mM was inhibitory.…”
Section: Discussionmentioning
confidence: 99%
“…of PS-containing vesicles (Fraley et al, 1980) and RBC ghosts (Hoekstra et al, 1985). However, Hoekstra et al (1985) have recently shown that the potential for Ca2+ and phosphate to induce fusion of RBC ghosts is extremely sensitive to the Ca2+ and phosphate concentrations and required at least 7 mM phosphate, while Ca2+ above 2 mM was inhibitory. Therefore, if one assumes that the membrane components responsible for RBC ghost fusion (the lipid component) are similar to those found in our TLE extracts, then fusion would not have been expected to occur since our routine Ca2+ and phosphate concentrations were below (3.3 mM) and above (5.0 mM) those required to facilitate fusion.…”
Section: Discussionmentioning
confidence: 99%
“…Human red blood cells (type A+) were obtained from the Red Cross Blood Bank. Ghosts were prepared (Hoekstra et al, 1983(Hoekstra et al, , 1985 by hypotonic hemolysis in 5 mM sodium phosphate buffer, pH 8.0. Prior to being resealed at 37 °C for 45 min in the presence of 1 mM Mg2+, albumin (5% w/v) was sequestered in the ghosts by a brief (15 min) incubation on ice.…”
Section: Methodsmentioning
confidence: 99%
“…Although the importance of calcium-phosphate and vitamin D for the bone is very well known and studied in detail, the studies on the effect of calcium phosphate and/or vitamin D, at membrane level are very limited [11][12][13][14][15]. In one of them, the findings of electron microscopy study suggested that calcium phosphate induces aggregation and membrane destabilization of cytoskeleton-free erythrocyte vesicles.…”
Section: Introductionmentioning
confidence: 99%
“…They found out that, the combination of calcium and phosphate drastically disrupts the membrane integrity of aggregated cytoskeleton-free vesicles at pH 7.8, which may have caused the destabilization of the vesicle membrane. The effect of calcium phosphate on human erythrocytes and erythrocyte ghosts was also studied by using light microscopy [12], fluorescence probe [13] and a kinetic assay [15]. Due to complexity of natural membranes, it is difficult to interpret the interaction between components.…”
Section: Introductionmentioning
confidence: 99%